Saturation corrections to dilute-dense particle production and azimuthal correlations in the Color Glass Condensate - S. Schlichting; V. Skokov (Physics Letters B, 2020)
We perform a numerical study of higher order saturation corrections to the dilute-dense approximation for multi-particle production in high-energy hadronic collisions in the framework of the Color Glass Condensate. We compare semi-analytical results obtained by performing a leading order expansion in the dilute field of the projectile with numerical simulations of the full Classical Yang-Mills dynamics for a number of phenomenologically relevant observables. By varying the saturation momentum of the target and the projectile, we establish the regime of validity of the dilute-dense approximation and assess the magnitude and basic features of higher order saturation corrections. In particular, we find that dilute-dense approximation faithfully reproduces dense-dense results if restricted to the range of its validity.